Analysis of Counseling Approaches in Addressing Students’ Learning Problems in Indonesia - Nur Mega Aris Saputra; Henny Indreswari; Lutfi Fauzan; Fitri Wahyuni; Muh Nur Alamsyah; Muhammad Rafli; Mohammad Aziz Shah Mohamed Arip (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2026)
The digital transformation in education has significantly impacted students’ learning processes in Indonesia. Uncontrolled use of technology has triggered various learning issues, including concentration difficulties, academic anxiety, low motivation, and internet addiction. This study aims to identify effective counseling approaches in addressing students’ learning problems in Indonesia and to analyze both learning challenges and the factors influencing intervention success. A Systematic Literature Review (SLR) method was employed, following PRISMA and Cochrane guidelines, synthesizing 29 selected studies published between 2010 and 2025. The findings indicate that counseling approaches such as individual counseling, group counseling, Cognitive Behavior Therapy (CBT), Rational Emotive Behavior Counseling (REBC), reality therapy, and self-management are effective in improving students’ independence, motivation, discipline, and in reducing academic anxiety and digital addiction. The success of these interventions is influenced by internal factors (emotions, motivation, and study habits) and external factors (family support, school conditions, and technology integration). This study concludes that action-oriented, structured, and contextually adaptive counseling approaches are essential in responding to the socio-digital challenges faced by students. The results of this review offer valuable insights for developing school counseling policies and professional counselor training programs that are responsive to the demands of digital-era learning.